Multicriteria adaptive routing in computer networks - Баранов, В. Л.; Мартынова, О. П. (Problems of Informatization and Control, 2008)
A method for adaptive routing in computer networks, which was based on multi-objective optimization of the weight of the branches of the graph modeling of nonlinear compromise scheme